When adding an unreactive metal enhances catalytic activity: NOx decomposition over silver-rhodium bimetallic surfaces - Inderwildi, O; Jenkins, S; King, D (2007)
Recent experiments indicate unexpectedly high catalytic activity for decomposition of NOx species over Ag-Rh nanoparticles, but the crucial role played by the coinage metal remains unclear. We have therefore performed ab-initio density functional calculations aimed at elucidating key features of NO surface chemistry on Ag, Rh, and Rh-Ag alloy substrates. Through investigation of thermochemistry and reaction barriers, and analysis of the alloy density of states, we explain the paradox that addition of an unreactive coinage metal can radically enhance the activity of a transition metal catalyst. © 2007 Elsevier B.V. All rights reserved.